FAKTOR PRODUCT QUALITY DAN FOOD SAFETY TERHADAP LOYALITAS KONSUMEN PADA RESTORAN JEPANG - Nazwa, Chika Salsabila; Pratama, Maulana Agung; Subagja, Ghia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
This research aims to find out how much influence product quality and food safety have on consumer loyalty in Japanese, restaurants, which in this research is Ichiban Sushi, outlet Bandar Lampung. In this research, two independent factors were, used as the main variables, namely Product Quality (X,) and Food Safety (X) and one dependent variable, namely Consumer Loyalty (Y). This research uses an explanatory research method with a quantitative approach. The population that is the subject of this research is consumers of Ichiban Sushi, outlet Bandar Lampung. Data was obtained from distributing questionnaires with a Likert scale. The sampling method used in this research was accidental sampling with a total of 100 respondents. Data were, analyzed using the multiple. linear regression method using SPSS for Windows version 25 software. Based on the research results, it shows that there, is a significant influence, between product quality and food safety on consumer loyalty with a greater influence on product quality with varied menu aspects and aspects. The lowest is the completeness of the dishes on the table. The suggestion in this research is that companies should focus more, on improving product quality through the performance, of the services provided, such as more quickly completing dishes on tables that are, almost finished or even incomplete.